Virulence genes and genetic diversity assessment of Shiga toxin-producing Escherichia coli O91 strains from cattle, beef and poultry products - Hernandez, Luciana Belén (2018)
Shiga toxin-producing Escherichia coli (STEC) O91 has ranked in the top five of the non-O157 serogroups most frequently associated with human cases. In order to gain insight into the genetic diversity of O91 Latin American STEC strains, we analyzed their virulence properties and carried out a subtyping assay. A panel of 21 virulence genetic markers associated with human and animal infections was evaluated and the relatedness among strains was determined by a multiple-locus variable-number tandem repeats analysis (MLVA) comprising 9 VNTR loci. Twenty-two STEC O91 isolated from cattle and meat food and belonging to 5 serotypes (O91:H21, O91:H8, O91:H14, O91:H28, O91:H40) were studied. Eight virulence profiles were obtained for the O91 STEC strains: 4 for O91:H21 plus one for O91:H8, O91:H14, O91:H28 and O91:H40. All strains contained ehxA and lpfA0113 genes and only both stx1-positive strains lacked saa, which encodes the STEC autoagglutinating adhesin. Other genes involved in adhesion were detected: ehaA (91%), elfA and espP (86%), ecpA (82%) and, hcpA (77%). The gene encoding the cytolethal distending toxin type-V (CDT-V) was found only in O91:H8 and O91:H21, being present in the majority (89%) of strains of this last serotype. MLVA typing divided the total number of strains into 12 genotypes, and 9 of them were unique to a single strain. No association was observed between the virulence profiles and the source of the strains. Although they lack the eae gene, most of the strains have the genetic potential to adhere to host cells through other structures and possess cdt-V, which has been found in STEC strains involved in serious diseases. The MLVA showed clonal relatedness among strains isolated from cattle belonged to a same dairy farm and suggested that the same clone remains circulating throughout the year and, on the other hand, the need to increase the number of VNTR loci which could allow a higher discrimination among O91:H21 isolates.